Representation of Muslim Women as Seen in American Advertisements: Ability, Egalitarianism, and Resistance - Moona Maghfirah (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2020)
Since Muslimah fashion has risen in the world, many companies are showing Muslim women who wear veiling their advertisements, including American brands advertisements. They are Nike, American Eagle, Covergirl, Fenty Beauty, and Gap. This case is important to be discussed, because it is completely opposite. America is well-known as Islamophobia country and hijab-Muslim woman as an identity of Islam religion. Therefore, the study aims to reveal the meaning of the Muslimah model in these advertisements. The method used in this study is a qualitative descriptive method and applies Roland Barthes semiotic theory and religification of commodities theory. This research found the meanings of Muslimah models refer to the current phenomena of Muslimah life such as the modern beauty and lifestyle of Muslimah, and the freedom in showing their status and skill, and the diversity in the representation of woman beauty. Three myths (ideologies) found in this research are a deconstruction of a negative stereotype of Muslimah in America, beauty standard, and egalitarianism values. Therefore, this research argues that the advertisement is an underground movement of Muslim women as their resistance to negative stigmas in American society by expressing their identities, ability, and egalitarianism values.